Male spiders control offspring sex ratio through greater production of female-determining sperm - Vanthournout, Bram (Proc Biol Sci, 2018)
Sex allocation theory predicts that when sons and daughters have different reproductive values, parents should adjust offspring sex ratio towards the sex with the higher fitness return. Haplo-diploid species directly control offspring sex ratio, but species with chromosomal sex determination (CSD) were presumed to be constrained by Mendelian segregation. There is now increasing evidence that CSD species can adjust sex ratio strategically, but the underlying mechanism is not well understood. One hypothesis states that adaptive control is more likely to evolve in the heterogametic sex through a bias in gamete production. We investigated this hypothesis in males as the heterogametic sex in two social spider species that consistently show adaptive female-biased sex ratio and in one subsocial species that is characterized by equal sex ratio. We quantified the production of male (0) and female (X) determining sperm cells using flow cytometry, and show that males of social species produce significantly more X-carrying sperm than 0-sperm, on average 70%. This is consistent with the production of more daughters. Males of the subsocial species produced a significantly lower bias of 54% X-carrying sperm. We also investigated whether inter-genomic conflict between hosts and their endosymbionts may explain female bias. Next generation sequencing showed that five common genera of bacterial endosymbionts known to affect sex ratio are largely absent, ruling out that endosymbiont bacteria bias sex ratio in social spiders. Our study provides evidence for paternal control over sex allocation through biased gamete production as a mechanism by which the heterogametic sex in CSD species adaptively adjust offspring sex ratio.